POLYMORPHISM OF THE APO-A AND APO-B GENES AND THE LIPID PROFILE OF PATIENTS WITH COVID-19: AN INTEGRATIVE REVIEW - da Silva, Anna Beatriz Oliveira; Teixeira, Dante Mafra Tourino; Soares, Antonio Avelino Ferreira; Bonasser, Larissa Sousa Silva; Gontijo, Bruna Rodrigues; Pereira, Alexandre Sampaio Rodrigues; Benito, Linconl Agudo Oliveira; da Silva, Izabel Cristina Rodrigues (Seven Editora, 2025)
Objective: to analyze the influence of polymorphisms of APOA and APOB genes with the lipid profile of patients with COVID-19. Method: the research was carried out in the databases Scholar Google, Biblioteca Virtual em Saúde - BVS, Portal de Periódicos CAPES, and PubMed, using the descriptors "Apo-B polymorphism AND SARS-Cov-2 AND COVID-19" and "Apo-A polymorphism AND Covid-19". We selected studies from 2020 that were compatible with the objective of the study. Results: an association was found between the polymorphism of Apo A-1 -75G/A (rs670) and lower levels of triglycerides (TG) in patients with COVID-19, whereas the polymorphism of Apo B (rs693) was associated with reduced levels of TG only when and codominance with SNP -75G/A (rs670). Conclusion: the polymorphisms of Apo A-1 and Apo B play a significant role in the prognosis and development of COVID-19, added to this is of paramount importance the investment in studies for so, the development of new therapeutic intervention strategies based on the patient’s genetic profile, in order to optimize treatment and increase survival of individuals in a critical state. DOI: https://doi.org/10.56238/sevened2025.037-032